Community Empowerment Based on VCO Oil Production Training in Balamoa Village - Taha, Nasim; Putri Damayanti, Adinda; Dewi, Karista; Syahbani, Nur Afni; Bakir, Fahmi (Journal of Engineering Science and Technology Management (JES-TM), 2026)
The community service program (KKN) of Alkhairaat University (Unisa) Group 131 in Balamoa Village, Dolo Barat District, Sigi Regency, Central Sulawesi, focuses on the production of Virgin Coconut Oil (VCO). This flagship program was held over two sessions on October 20 and 24, 2025. The activity aimed to enhance the knowledge and skills of local residents, particularly housewives, in processing coconuts into high-economic-value products. The program was implemented using a lecture and hands-on practice method. The results show high enthusiasm among participants and improved understanding of hygienic and marketable VCO production techniques. This activity has the potential to serve as the foundation for sustainable home-based businesses using local coconut resources